Pelatihan Pengembangan Bahan Ajar Bahasa Inggris kepada Calon Pengajar di Universitas Persatuan Islam Bandung - Syaepul Uyun, Aip (Ma'soem University, 2024)
Teaching material development is a comprehensive process for determining the teaching material needs of a group of learners. In practice, there are two important things that teachers need to know in an effort to develop teaching materials. The first is knowledge of material needs analysis procedures, and the second is knowledge of the material coverage mandated by the government. These two factors are important to understand in order to develop teaching materials that suit student needs. However, in reality, there are still many teachers who do not understand the process of developing teaching materials well, therefore community service in the form of seminars on developing English teaching materials is carried out. This community service was carried out in the English Education Department at Universitas Persatuan Islam Bandung. Participants are all students of year one and two English Language Education students. The results of the activity showed that prospective teacher students gained knowledge about the procedure for developing English teaching materials so that the material developed was in accordance with student needs.